PHYSIOTHERAPY SERVICE WITHOUT STANDARDIZED OPERATING PROCEDURES FROM PHYSIOTHERAPIST’S PERSPECTIVE: A CASE STUDY - Triana Karnadipa (Universitas Airlangga, 2021)
Background: Treatment variations have been considered as a sign of an inappropriate healthcare service whether due to the underuse or the overuse of resources. To reduce these variations, establishing and implementing well-developed standardized operating procedures (SOPs) and evidence-based standardized clinical guidelines is required. A rehabilitation unit for children with disabilities in Makassar did not implement any SOPs or standardized clinical guidelines in their service and treatment. This conduct may have an adverse effect on physiotherapists’ professionalism.Aims: The study aimed to explore the possible impact of community-based rehabilitation (CBR) practice with no SOPs and evidence-based standardized clinical guidelines on the physiotherapists. Method: This study was a qualitative case study. The CBR unit was observed for 278-hours and the study conducted three semi-structured interviews. Three physiotherapists voluntarily participated in the study. Open, axial, and selective coding were conducted to encode the interview findings. The findings from observation encoded interview, field, and self-reflective notes were triangulated, analyzed thematically, and illustrated by the explorative model.Results: Working with no SOPs and guidelines was associated with variations in procedures by physiotherapists, irregularity in their treatment choices, liability feeling toward errors making, and Low self-confidence in their professionalism.Conclusion: Working without SOPs and guidelines was associated with psychological exertion of the physiotherapists. They showed uncertainty in their professional capabilities as a physiotherapist. It is recommended for YPAC Makassar city to develop SOPs and evidence-based standardized clinical guidelines for their organization.Keywords: children, community-based rehabilitation, disability, guidelines, standard-operating procedure